Personal Attitude, Subjective Norm, and Perceived Behavioral Control: Differentiating Factors of Entrepreneurial Intention of High School Students who are Joining and not Joining the Entrepreneurship Education in an International School - Turra, Gracia M. S.; Melinda, Tina (KnE Social Sciences, 2021)
The Indonesian government provides an incentive to develop entrepreneurship to boost economic growth and to prepare for the ASEAN Economic Community (AEC) by increasing the entrepreneurial intentions of the Indonesian people. One way to develop entrepreneurial intentions is to apply entrepreneurship education early on. The Singapore National Academy (SNA) is an international school that offers the Business subject from grades 9 - 12. SNA also offers another form of entrepreneurship education, which is the Enterprising co-curricular activity (CCA) that is more focused on projectbased learning. This study was conducted in SNA, which has students of various ethnic groups who mostly have parents with an entrepreneurial background. The purpose of this study was to elucidate whether personal attitude (PA), subjective norm (SN), and perceived behavioral control (PBC) affect the intention of entrepreneurship of students who are joining CCA Enterprising and students who are not joining CCA Enterprising in SNA. The sample consisted of 60 respondents, including 30 students of CCA Enterprising and 30 students who were not in CCA Enterprising, who were recruited using a saturated sampling technique. Based on the results of the discriminant analysis with the stepwise method, all variables (subjective norm, personal attitude and perceived behavioral control) affected the entrepreneurial intention of students who were joining CCA Enterprising compared with students who were not joining CCA Enterprising. There was a significant difference between the entrepreneurship intentions of those in CCA Enterprising compared with those who were not. Keywords: entrepreneurship education, personal attitude, subjective norm, perceived behavioural control, entrepreneurial intention